2015
DOI: 10.1111/jfb.12827
|View full text |Cite
|
Sign up to set email alerts
|

Segregation or aggregation? Sex‐specific patterns in the seasonal occurrence of white sharks Carcharodon carcharias at the Neptune Islands, South Australia

Abstract: The seasonal patterns of occurrence of male and female white sharks Carcharodon carcharias at the Neptune Islands in South Australia were reviewed. Analyses of a 14 year data series indicate that females seasonally aggregate in late autumn and winter coinciding with the maximum in-water availability of lactating female long-nose fur seals and seal pups. During this period, observed male:female sex ratios were similar; whereas during late spring and summer, males continued to visit, but females were rarely reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Sex-based differences in migratory patterns of juvenile and adult white sharks have been observed throughout their range, e.g. the northeast and central Pacific 13,44 , Australia 45 and South Africa 46 . Male-biased dispersal has previously been identified between Australasian and South African white sharks based on contrasting maternally and biparentally inherited genetic markers 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Sex-based differences in migratory patterns of juvenile and adult white sharks have been observed throughout their range, e.g. the northeast and central Pacific 13,44 , Australia 45 and South Africa 46 . Male-biased dispersal has previously been identified between Australasian and South African white sharks based on contrasting maternally and biparentally inherited genetic markers 47 .…”
Section: Discussionmentioning
confidence: 99%
“…For many white shark populations around the world, researchers have reported male-dominant sex ratios (Chapple et al 2011;Domeier and Nasby-Lucas 2012;Kock et al 2013;Bruce and Bradford 2015). In this study, we estimated two males for every female shark in our sample over a period of 9 years after probabilistically assigning sex to individuals that remained unsexed throughout the study period.…”
Section: Sex Ratiomentioning
confidence: 99%
“…Chapple et al (2016) reported that annual temporary emigration is more prevalent for females (0.57, 95% confidence interval (CI) = 0.40-0.72) than males (0.015, 95% CI = 0.00-0.31). This sex-specific unavailability for sampling occasions can inherently bias the observed sex ratio over a long study period and needs to be considered when conducting population dynamic studies (Bruce and Bradford 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Animal aggregations can yield some of the most striking spatial patterns in nature. They are observed in almost all taxa (Ims 1988;Sumpter 2006;Bruce and Bradford 2015;Venkataraman et al 2017), and may comprise several species (Heymann and Buchanan-Smith 2000;Goodale et al 2010). In some cases, they result directly from the existence of large-scale resource heterogeneity, but in others, animals aggregate more than what would be expected on the basis of resource distribution alone (Brown and Orians 1970;Jeanson et al 2005).…”
Section: Introductionmentioning
confidence: 99%